2017
DOI: 10.1016/j.jams.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Contact Tools in Japanese Acupuncture: An Ethnography of Acupuncture Practitioners in Japan

Abstract: This study aimed to identify procedural elements of Japanese acupuncture, describe these elements in detail, and explain them in terms of the key thematic category of treatment principles. Between August 2012 and December 2016, ethnographic fieldwork was conducted in Japan. In total, 38 participants were recruited by chain referral and emergent sampling. Data was collected through participant observation, interviews, and by analyzing documents. A total of 22 participants agreed to clinical observation; 221 tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Since the trial found a significant improvement in all three acupuncture treatment arms compared to the no-acupuncture arm, the trial demonstrated that, for the treatment of the shoulder pain targeted by the trial, it is not necessary to insert needles for the treatment to be effective. There are a number of noninsertion needling techniques and systems in acupuncture [2,9,10], and this trial helps to demonstrate the potential use of these in the treatment of shoulder pain.…”
Section: Methods Mattermentioning
confidence: 99%
“…Since the trial found a significant improvement in all three acupuncture treatment arms compared to the no-acupuncture arm, the trial demonstrated that, for the treatment of the shoulder pain targeted by the trial, it is not necessary to insert needles for the treatment to be effective. There are a number of noninsertion needling techniques and systems in acupuncture [2,9,10], and this trial helps to demonstrate the potential use of these in the treatment of shoulder pain.…”
Section: Methods Mattermentioning
confidence: 99%
“… Round ended, blunt tools or sharp pointed needles with touch or light pressure applications (Japanese Shonishin, contact needling, sanshin), 7 , 9 , 11 , 12 , 13 , 14 using thin needles (0.12–0.18 mm gauge) without insertion common in Japanese Meridian Therapy. 12 , 15 , 16 , 17 Round ended, blunt tools or sharp pointed needles with pressure, potentially with discomfort or pricking sensations (e.g.…”
Section: Examples Of the Varieties Of Contemporary ‘Acupuncture’ Methodsmentioning
confidence: 99%
“…Shonishin, contact needling, Toyohari) . 7 , 9 , 10 , 11 , 12 Thin needles (0.12–0.18 mm gauge) shallowly inserted (1–3 mm) e.g. the Japanese ‘chishin method,’ 8 , 15 , 18 or short thin needles (0.20 mm gauge) inserted shallowly and taped to remain in place.…”
Section: Examples Of the Varieties Of Contemporary ‘Acupuncture’ Methodsmentioning
confidence: 99%
See 2 more Smart Citations